The Haliti-Paresí child's knowledge about hantavirus in artistic expressions - Ana Cláudia Pereira Terças; Vagner Ferreira do Nascimento; Thalise Yuri Hattori; Érica Baggio; Marina Atanaka; Elba Regina Sampaio de Lemos (Universidad de Alicante, 2018)
Objective: To identify the knowledge of Haliti-Paresí children about hantaviruses through artistic expressions. Method: This is a descriptive-interpretative and qualitative study conducted with nine children of the Haliti-Paresí ethnicity through art therapy. The analysis of the design was performed using the single analysis recording technique. Results: We analyzed 14 graphic records of nine children in three categories: physical and social environment, knowledge about the transmission of hantaviruses and knowledge about the disease/lethality. In the artistic expressions the presence of the reservoir of the disease was observed and the clinical severity with hospitalization images. Conclusion: The artistic productions of the children revealed the importance of educational and preventive measures that contribute to the improvement of the quality of life.